Botanical and genetic characteristics of Celtis australis L. and Celtis occidentalis L. grown in Egypt - Taha Shahat M.A. El-Alfy; Hamida Mohamed A. El-Gohary; Nadia Mohamed Sokkar; Sahar Abd El-Tawab; Dalia Adel Mohamed Al-Mahdy (Faculty of Pharmacy, Cairo University, 2011)
Celtis australis L. and Celtis occidentalis L. are deciduous ornamental trees, grown in Egypt. This study presents a comparative investigation of the botanical features of the stems, stem barks and leaves of both plants. Furthermore, the DNA of both plants was extracted from leaf samples and analyzed using 10 decamer random primers. A total of 159 random amplified polymorphic DNA (RAPD) markers were identified. Seed protein profiling was also performed and revealed low variation in both plants' SDS-PAGE profiles.